Analisis Kepuasan Pengguna Laboratorium Pendidikan Administrasi Perkantoran Fakultas Keguruan Dan Ilmu Pendidikan Universitas Sebelas Maret - Aster Cahyaning Tyas; Tutik Susilowati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research aims to (1) determine the satisfaction of students of the Office Administration Education Program 2021 and 2022 cohorts as laboratory users. (2) identify the attributes that are high priority and low priority in student satisfaction as laboratory users. This research is a quantitative study involving the population of active student users of the laboratory facilities in the Office Administration Education Program at the Faculty of Teacher Training and Education, Universitas Sebelas Maret, namely students from the 2021 and 2022 cohorts totaling 280 students. Sampling from the quantitative data population used probability sampling with Simple Random Sampling technique involving 155 students. Data collection was conducted by distributing research questionnaires. Data analysis technique used the important performance analysis (IPA) method with the assistance of IBM SPSS version 22 software. The research results indicate that (1) students are not yet satisfied with the laboratory services of PAP FKIP UNS as evidenced by student satisfaction for all attributes being < 100% with an average conformity rate of 70%. The gap analysis results indicate that all statements have negative values with an average performance of 2.66 and an average importance of 3.79. (2) There are high priority attributes with an average importance > 3.79 but an average performance < 2.66, namely the competence of laboratory personnel, completeness, and suitability of laboratory equipment. Meanwhile, low priority attributes have an average importance < 3.79 and an average performance < 2.66, including the modernity of laboratory equipment, timeliness of service, readiness and responsiveness of laboratory personnel, as well as the availability of first aid kits in the laboratory.